Answer:
5x+3y
Step-by-step explanation:
2x+3x=5x since they have the same variable.
y+2y
1y+2y u can put a 1 so that would be 3y
5x+3y
Answer:
Step-by-step explanation:
#22
<h3>Given </h3>
- Equation x² -4x + 1 = k(x - 4) with equal roots
<h3>To find</h3>
<h3>Solution</h3>
<u>The equation in standard form is:</u>
- x² -4x + 1 = k(x - 4)
- x² - 4x - kx + 1 + 4 = 0
- x² - (k + 4)x + 5 = 0
<u>When the quadratic equation has equal roots its discriminant is zero</u>
- D = 0
- b² - 4ac = 0
- (k + 4)² - 4*5 = 0
- (k + 4)² = 20
- k + 4 = ± √20
- k = - 4 ± √20
- or
- k = -4 ± 2√5
Answer:
Analyze then add
Step-by-step explanation:
Basically, just analyze the lengths of the sides, and then add them together for the perimeter
Thank me later :)
━━━━━━━☆☆━━━━━━━
▹ Answer
<em>6(1-r)</em>
▹ Step-by-Step Explanation
8 - (6r + 2)
8 - 2(3r + 1)
2(4 - (3r + 1))
2(4 - 3r - 1)
2(3 - 3r)
2 * 3(1 - r)
6(1 - r)
Hope this helps!
- CloutAnswers ❁
Brainliest is greatly appreciated!
━━━━━━━☆☆━━━━━━━